الاستفادة من الطاقة الشمسيّة في تحسين مردود محطّات توليد الطّاقة المركّبة - Roza Ali Deeb (Tishreen University, 2019)
الاستفادة من الطاقة الشمسيّة في تحسين مردود محطّات توليد الطّاقة المركّبة (بخاريّة -غازيّة) لإنتاج الطاقة الكهربائية روزا علي ديب إن أزمات الطاقة العالمية في السنوات الأخيرة،, ومشكلة تلوث البيئة أعطت شعوراً عاماً بأهمية البحث الجدي والمستمر عن الطّاقات المتجددة والبديلة, كما إنّ ارتفاع أسعار الوقود وتوقع نضوبه يجعلان من الضروري التفكير باستخدام الطّاقة الشّمسية في إنتاج الطّاقة الكهربائيّة، والمساعدة بتقليل استهلاك الوقود في محطات توليد الطّاقة الكهربائية التقليدية و المركبة. نقدم في هدا البحث دراسة تحليلية  وبرمجية لدمج محطة الطّاقة الشّمسية مع محطّات توليد الطّاقة المركبة (غازية - بخارية )،من أجل الاستفادة من الطّاقة الشّمسية كمصدرٍ مساعدٍ لتسخين الماء وتوليد وتحميص البخار في محطّات توليد الطّاقة المركبة، بهدف التقليل من استهلاك الوقود، والدي بدوره يؤدي إلى التوفير الاقتصادي من جهةٍ، والتقليل من تلوث البيئة من جهةٍ أخرى. وكذلك وضع خوارزميّة من أجل حساب كمية الحرارة الشّمسية الصافيّة المجمّعة، وثم تحويلها إلى برنامج كمبيوتر بلغةVisualC++ .وكذلك عرض للنتائج الحاصلة. The global energy crises of recent years and the problem of environmental pollution have given a general sense of the importance of serious and continuous research on renewable and alternative energies. Rising fuel prices and their forecasting make it necessary to consider using solar energy to produce electricity and help reduce fuel consumption in power plants Electric and conventional In this research we present a descriptive and analytical study of the integration of a solar plant with compound power plants (gas-steam) to utilize solar energy as an auxiliary source for water heating and steam generating and roasting in compound power plants, in order to reduce fuel consumption. In torn , this leads to an economy an one hand and reducing the pollution of the environment on the other . It also develops an  to economize on the one hand, and to reduce pollution of the environment on the other. To be algorithm to calculate the amount of net solar heat collected, and then converted to a computer program language VisualC ++, And to view the results obtained.